EFFECTIVENESS OF INDIVIDUAL COUNSELING SERVICES USING A COGNITIVE BEHAVIOR THERAPY (CBT) APPROACH THROUGH DEEP SELF INSTRUCTION TECHNIQUES REDUCES LEARNING DIFFICULTY - Tanjung, Asbih Fahrezi; Harahap, Ade Chita Putri (Universitas Islam Negeri Syekh Ali Hasan Ahmad Addary Padangsidimpuan, 2024)
The purpose of writing this article is to determine the effectiveness of individual counseling services using the Cognitive Behavior Therapy (CBT) approach through self-instruction techniques in reducing learning difficulties at Madrasah Aliyah Negeri 1 Medan. Quantitative research is guided by a pre-test plan and a single-group pre-test-post-test plan. On the analyst's learning difficulties scale, 26 of the 28 statement items are used in a test of legitimacy and firm quality. The results are considered substantial if the determined r exceeds the table r value, namely 0.2329 at a 5% level of significance. For the reliability test, Cronbroach alpha data was collected with a Cronbroach Alpha value greater than 0.05 (0.999 0.05). The research population at Madrasah Aliyah Negeri 1 Medan includes more than three classes in class X (ten), namely classes X5, X7, and X8. Purposive testing techniques were used to select five students with high levels of learning difficulties from 110 students in each of the three classes. The Wilcoxon Marked Positions Test was used to test the data. The results of this research show that the significance value is asymptotic. Sig(2-follow) values greater than 0.05 or 0.005 It is reasonable to assume that independent, individual tutoring services are effective in overcoming student learning difficulties.